Improving Teacher’s Pedagogic On Learning Evaluation At SDN 20 Mambok - Yasinta Lisa; Nelly Wedyawati; Wa Ode Ritna Yuniyr Ullah (International Journal of Public Devotion, 2018)
Teachers have a very important role in determining the quantity and quality of teaching in improving the quality of national education. The efforts to improving the quality process and learning outcomes are part of efforts to improve the quality of education through the evaluation system. Therefore, the teachers’ ability in planning evaluation is absolutely necessary. SD Negeri 20 Mambok is one of the primary schools that is located in Sintang which has been established since 1981. They followed training and course for self-development for learning evaluation infrequently. Based on those reasons, the author chooses the theme of this activity or PKM with SD Negeri 20 Mambok as a partner. The method used is course and Training. Implementation of this PKM is a day. The result of the activity or PKM shows that there is interest from the participant in following the activity which is shown by the number of participants exceeding the planned target and the improvement of the participant's understanding and skill in designing and analyzing the evaluation instrument of learning in the good category. The improvement in participants' understanding and skills can be seen in showing in practicum and do the task during the event.